Stomatognati sistem: Anatomija, fiziologija, razvoj, histologija - Fekonja, Anita (University of Maribor Press, 2025)
Stomatognathic System: Anatomy, Physiology, Development, Histology. The book The Stomatognathic System includes information that students of study programm Dental Medicine of the Faculty of Medicine University of Maribor study in the course Tooth Morphology (Oral Anatomy and Physiology). The stomatognathic system is a fundamental field of dental medicine, so knowledge of oral anatomy, physiology, histology and development is important to understand the structure and function of the stomatognathic system. Figures are added to the text for easier understanding. The textbook also includes examples from clinical practice related to the area under consideration.